2007
DOI: 10.1002/chin.200744172
|View full text |Cite
|
Sign up to set email alerts
|

New Syntheses of Tetrazolylmethylphenylalanine and O‐Malonyltyrosine as pTyr Mimetics for the Design of STAT3 Dimerization Inhibitors.

Abstract: New syntheses of tetrazolylmethylphenylalanine and O-malonyltyrosine as pTyr mimetics for the design of STAT3 dimerization inhibitors..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Several authors have reported the development of Stat3 inhibitors that incorporate phopshotyrosine or phosphotyrosine mimic 71-76. These compounds did not contain glutamine or a mimic and displayed low affinity for the target, as judged by electrophoretic mobility shift assays or fluorescence polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the development of Stat3 inhibitors that incorporate phopshotyrosine or phosphotyrosine mimic 71-76. These compounds did not contain glutamine or a mimic and displayed low affinity for the target, as judged by electrophoretic mobility shift assays or fluorescence polarization.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 300 MHz) δ1.31À1.38 (m, 6H), 2.58 (s, 3H), 4.17À4.28 (m, 4H), 7.31 (d, J = 8.7 Hz, 2H), 7.97 (d, J = 8.7 Hz, 2H). 13 C NMR (CDCl 3 , 75.0 MHz) δ 16.0, 26.5, 64.8, 82.5, 119.9, 130.3, 133.9, 154.4, 196.6. HRMS (M þ H) calcd, 273.0892; found, 273.0965.…”
Section: Synthesis Of 4-diethylphosphoryloxyacetophenone 21mentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 300 MHz) δ1.32À1.37 (m, 6H), 1.51 (s, 9H), 2.50 (s, 3H), 4.16À4.27 (m, 4H), 6.0 (s, 1H), 7.2 (d, J = 8.7 Hz, 2H), 7.43 (d, J = 8.7 Hz, 2H). 13 Synthesis of Pentachlorophenyl (E)-3-(4-Diethoxyphosphorylphenyl)but-2-enoate, 24. A solution of 23 (2.00 g, 6.4 mmol), pentachlorophenol (1.9 g, 7.0 mmol), DCC (1.6 g, 7.7 mmol), and DMAP (0.08 g, 0.64 mmol) in 100 mL of ethyl acetate was stirred at room temperature for 24 h. The mixture was filtered through Celite and the solvent removed in vacuuo.…”
Section: Synthesis Of 4-diethylphosphoryloxyacetophenone 21mentioning
confidence: 99%
“…[33] Substitution of the phosphate group with an O -methylenecarboxylic acid ( 23b ) or tetrazole ( 23c or 23d ), a more lipophilic bioisostere of a carboxylic acid, was poorly tolerated. It is suggested that mono-anionic pTyr mimetics are incapable of forming as many hydrogen bonds and salt bridges with the two positively charged amino acid residues in the pTyr binding pocket, specifically Lys 591 and Arg 609, compared with pTyr.…”
Section: Junctures For Stat3 Molecular Interventionmentioning
confidence: 99%